Genetic attributes of blood‐derived subtype‐C HIV‐1 tat and env in India and neurocognitive function. Issue 1 (22nd October 2013) - Tilghman, Myres W.; Bhattacharya, Jayanta; Deshpande, Suprit; Ghate, Manisha; Espitia, Stephen; Grant, Igor; Marcotte, Thomas D.; Smith, Davey; Mehendale, Sanjay
Abstract Genetic elements in HIV‐1 subtype B tat and env are associated with neurotoxicity yet less is known about other subtypes. HIV‐1 subtype C tat and env sequences were analyzed to determine viral genetic elements associated with neurocognitive impairment in a large Indian cohort. Population‐based sequences of HIV‐1 tat (exon 1) and env (C2‐V3 coding region) were generated from blood plasma of HIV‐infected patients in Pune, India. Participants were classified as cognitively normal or impaired based on neuropsychological assessment. Tests for signature residues, positive and negative selection, entropy, and ambiguous bases were performed using tools available through Los Alamos National Laboratory (http://www.hiv.lanl.gov) and Datamonkey (http://www.datamonkey.org). HIV‐1 subtype C tat and env sequences were analyzed for 155 and 160 participants, of which 34–36% were impaired. Two signature residues were unique to impaired participants in exon 1 of tat at codons 29 (arginine) and 68 (proline). Positive selection was noted at codon 29 among normal participants and at codon 68 in both groups. The signature at codon 29 was also a signature for low CD4+ (<200 cells/mm3) counts but remained associated with impairment after exclusion of those with low CD4+ counts. No unique genetic signatures were noted in env. In conclusion, two signature residues were identified in exon 1 of HIV‐1 subtype C tat that were associated with neurocognitive impairment in India and not completely accounted for by HIV disease progression. These signatures support a linkage between diversifying selection in HIV‐1 subtype C tat and neurocognitive impairment. J. Med. Virol. 86:88–96, 2014. © 2013 Wiley Periodicals, Inc.